Regional Feature Product Development Management Using Data Management Using Networked Websites in Assisted Villages in Realizing the Tridharma of Politeknik Negeri Medan - Agus, Rizal; Sari, Marliana; Barus, Enny Segarahati; Zuhirsyan, Muhammad; Lubis, M. Rizqi (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2024)
This research aims to carry out database management according to market needs and predetermined entities/variables, to be used as data storage for profiles of assisted villages based on superior village products and to redesign a web-based information system that presents profiles of assisted villages based on superior products and village connectivity. the. The research method used in database design and information system design uses descriptive qualitative methods by conducting focus group discussions with P3M Polmed administrators and conducting in-depth interviews with six village heads/secretaries in designing the prototype. This research produces a design for a networked website-based information system with the addition of creating the location and knowing the distance between one village and another, which presents a profile of the target village based on superior products that can be accessed via a network of websites and produces a mandatory output in the form of a book with an ISBN.